Possibilities of using selected visualization methods for historical analysis of sporting event – an example of stage cycling race Tour de France - Bačík, Vladimír; Klobučník, Michal (Quaestiones Geographicae, 2018)
Nowadays, we are facing an enormous amount of data which are being produced by different systems. These must be effectively stored and visualized in order to enable their proper interpretation. In our research, we attempted to use circular data visualization applied on the Tour de France cycling race. Since this competition has over 100 years of history, a variety of data is available. Using the chord diagrams we tried to illustrate the long-term development of this race, with an emphasis on its spatial and sport aspects. Spatial dimension is characterised by the large number of stages and mountain climbs in such locations which altogether enhance the meaning of this major sporting event, while sport aspects aim to capture the significant personages on the scorecard. Circular visualization has found its application in many disciplines (genetics, demography, medicine, etc.). In our contribution, we point out its importance also in the visualization of the historical milestones of the most important multi-stage cycling event in the world.